A possible explanation on the changes in the spatial structure of ENSO from CMIP3 to CMIP5. Issue 1 (8th January 2014) - Yeh, Sang‐Wook; Ham, Yoo‐Geun; Kirtman, Ben P.
Abstract [1] This study examines changes in the structure of El Niño‐Southern Oscillation (ENSO) amplitude using the historical climate simulations of the World Climate Research Program Coupled Model Intercomparison Project (CMIP) phase‐3 and phase‐5 coupled general circulation models (CGCMs). The analysis focuses on the "so‐called" Bjerknes feedback. The Bjerknes feedback affects the sea surface temperature (SST) variability differently between the CMIP3 and CMIP5 models. In the CMIP5 models, the strength of the Bjerknes feedback is associated with the amplitude of ENSO, whereas the changes in the strength of Bjerknes feedback are not associated with changes in ENSO amplitude in CMIP3 CGCMs. The relationship between the Bjerknes feedback and the SST anomaly variance is suggested as a possible explanation for the eastward shift in the SST anomaly variance in CMIP5 relative to CMIP3.